Assessment of general aviation airport pavement conditions in Kansas - Villarreal, Jose A. (Kansas State University, 2009)
The objective of this research project was to assess the condition of general aviation airport pavements in Kansas. The study was also intended to form the basis for a pavement management system (PMS). A total of 137 runways from 107 airports across the state were surveyed. MicroPAVER, a PMS system developed by the U.S. Army Corps of Engineers, was selected as the platform for the PMS. An inventory database was developed for all runways in the network. Information about the construction and maintenance history was entered into the MicroPAVER database. On-site surveys were conducted between the months of May and July of 2008 to assess pavement conditions in terms of the Pavement Condition Index (PCI), following the methodology outlined by ASTM D 5340-04 and adopted by the Federal Aviation Administration (FAA). Approximately 68% of the sections surveyed were in “good” to “satisfactory” condition. Almost one-third of the network can be rated as “good.” About 21% of the sections studied were in “fair” condition. Overall, the condition of the network can be rated as “satisfactory.” A condition prediction curve was developed for each of the two different types of surfaces. From the prediction curves created using MicroPAVER, it was estimated that the number of branches rated as “good” could decrease by 50% by 2010. As much as 44% of the network could have a rating of “fair” by 2013 if the sections receive only routine maintenance. Two budget scenario comparison reports developed show that the 108 runways of the 78 general aviation airports eligible for FAA funding in Kansas could be brought to a “satisfactory” rating or above (i.e. average PCI ≥ 70) by spending approximately $15 million on average per year for the next five years.
Keywords: Airport Pavement; MicroPAVER; Pavement Management System; Runway; Condition Prediction; Engineering, Civil (0543)